Allopurinol: insights from studies of dose–response relationships. (3rd April 2017) - Day, Richard O.; Kannangara, Diluk R.W.; Stocker, Sophie L.; Carland, Jane E.; Williams, Kenneth M.; Graham, Garry G.
ABSTRACT: Introduction : Gout is the most common inflammatory arthritis in men and is increasingly prevalent. Allopurinol is very effective at reducing plasma urate concentrations to a level sufficient to dissolve monosodium urate crystals. However, many patients fail to achieve a sufficient therapeutic response to allopurinol. Areas covered : This review covers the metabolism and pharmacokinetics of allopurinol and its active metabolite, oxypurinol and how these factors affect the plasma concentrations of urate at initiation and during long-term therapy with allopurinol. Significant aspects discussed are the importance of adherence to allopurinol therapy, allopurinol hypersensitivity reactions and insights into hyperuricemia. Expert opinion : The initial dosage of allopurinol should be low, particularly in patients with renal impairment. The dose should then be increased slowly until plasma concentrations of urate are sufficient to dissolve monosodium urate crystals (≤ 0.36 mmol/L). For this target, the maintenance dose of allopurinol can be estimated from the equation: Dose = 1413*(Up -0.36) where Up is the pre-treatment concentration of urate. Poor adherence is a major factor limiting successful therapy with allopurinol; however, its use can be improved considerably by education of patients and clinicians. Allopurinol is generally well tolerated and screening for genetic factors predictive of allopurinol hypersensitivity reactions can now be undertaken.